2020
DOI: 10.1021/acs.organomet.0c00094
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclic Sulfoxide–Alkene Hybrid Ligands for Chiral Rh(I) Complexes: The “Matched” Diastereomer Catalyzes Asymmetric C–C Bond Formations

Abstract: Deprotonation of phenyl-dibenzo[b,f]tropylidene 8 with LDA/t-BuOK followed by quenching with either diastereomers of inexpensive glucose-based t-Bu-sulfinates (R)-or (S)-11 affords a sulfoxidealkene hybrid ligand as diastereomeric pairs (S S ,S C )-9 / (S S ,R C )-10 and (R S ,R C )-9 / (R S ,S C )-10, respectively, which via chromatographic/recrystallization may be separated into the four isomers. The optically pure diastereomeric ligands (S S ,S C )-9 and (S S ,R C )-10 react with [RhCl(coe) 2 ] 2 to form th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…We also note that these Ir­(I) and Ir­(IV) complexes are robust and air-stable in the solid state and connect to a formal three-electron reservoir. Complex 9 is not only the first structurally characterized Ir­(IV) sulfoxido complex but also a rare example of an oxidizing high-valent late transition metal iodido complex with an apparent metal–ligand hard–soft mismatch . Soluble iridium iodido complexes are catalysts for a variety of very important reactions, such as BP’s Cativa process (the state of the art for acetic acid production) or Syngenta’s ( S )-metolachlor process (the world’s largest scale enantioselective reaction), in which the presence of iodine at some stage in the catalytic cycles may be assumed.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that these Ir­(I) and Ir­(IV) complexes are robust and air-stable in the solid state and connect to a formal three-electron reservoir. Complex 9 is not only the first structurally characterized Ir­(IV) sulfoxido complex but also a rare example of an oxidizing high-valent late transition metal iodido complex with an apparent metal–ligand hard–soft mismatch . Soluble iridium iodido complexes are catalysts for a variety of very important reactions, such as BP’s Cativa process (the state of the art for acetic acid production) or Syngenta’s ( S )-metolachlor process (the world’s largest scale enantioselective reaction), in which the presence of iodine at some stage in the catalytic cycles may be assumed.…”
Section: Discussionmentioning
confidence: 99%
“…For the sake of comparison and in order to assess the influence of the free electron pair of nitrogen on the stereodynamics of the azepine backbone, we also analyzed the inversion of the tropylidene analogue 8 (see Figure ). This backbone is encountered, e.g., in the sulfoxide-alkene ligand ( S S , S C )- 9 , and while 8 is a planar-chiral molecule in the solid state, in 9 , the chirality resides on the stereogenic C1 atom. Structure 9 is isoelectronic with azepine derivatives 3 and 4 (vide supra).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Compound VIII has gained the status of “privileged ligand”, and in an effort to develop this architecture further, we found that phenyl-substitution on the alkene function in IX and X effectively installs planar chirality in addition to the stereogenic P- or S-donor groups. Such diastereomerically and enantiomerically pure ligands form chiral metal complexes that catalyze a number of asymmetric transformations with up to 99% ee . We found that in these systems, the planar chirality of the alkene function is the overwhelming stereochemical director .…”
Section: Introductionmentioning
confidence: 93%
“…In 2020, Chelouan, Dorta, and co-workers reported tricyclic sulfoxide-alkene ligands in the asymmetric Hayashi–Miyaura reaction of cycloalk-2-enones with arylboronic acids (Scheme 34 ). 56 Ligand L61 was involved in the catalytic addition of arylboronic acids to the cyclic Michael acceptors with enantioselectivity up to 99% ee. Experimental studies concluded that stereology and electronics (leading to trans effects in square planar Rh(I) intermediates) played a role in the Hayashi–Miyaura reaction.…”
Section: Chiral Sulfoxides As Ligands In Metal-catalyzed Asymmetric C...mentioning
confidence: 99%